Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/biomedicines9070713
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Innate Immune Cell Programming

Abstract: Extracellular vesicles (EV) are a heterogeneous group of bilipid-enclosed envelopes that carry proteins, metabolites, RNA, DNA and lipids from their parent cell of origin. They mediate cellular communication to other cells in local tissue microenvironments and across organ systems. EV size, number and their biologically active cargo are often altered in response to pathological processes, including infection, cancer, cardiovascular diseases and in response to metabolic perturbations such as obesity and diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…For this reason, standardization of an effective method is in high demand in the current scenario. In this Review, we have indicated the potential of EVs in human physiology and further discussed the mechanism behind specific RNA incorporation inside EVs with a perspective on immune escape and colorectal cancer outcome. Besides the base sequence information on specific RNAs, a recent investigation detected the glycosylation modification on RNA surfaces. Bertozzi’s lab proposed that the glycosyl groups decorate on RNA surfaces in a similar way to proteins .…”
Section: Future Outlookmentioning
confidence: 99%
“…For this reason, standardization of an effective method is in high demand in the current scenario. In this Review, we have indicated the potential of EVs in human physiology and further discussed the mechanism behind specific RNA incorporation inside EVs with a perspective on immune escape and colorectal cancer outcome. Besides the base sequence information on specific RNAs, a recent investigation detected the glycosylation modification on RNA surfaces. Bertozzi’s lab proposed that the glycosyl groups decorate on RNA surfaces in a similar way to proteins .…”
Section: Future Outlookmentioning
confidence: 99%
“…Cargo loading is an important aspect of EV biogenesis as it can change under pathological conditions leading to up- or downregulation of certain genetic material (DNA and miRNA) as well as proteins, enzymes and lipids . Studies have already shown that ocular EVs, similar to EVs elsewhere in the body, are heterogeneous in nature and may contain various cargo such as genetic material, lipids, proteins and small metabolites. , Other enriched EV cargo includes cholesterol, sphingomyelin, ceramide, and lipid raft proteins. , Given the varying cargo between different EVs, scientists have developed a consortium of EV databases including ExoCarta, Vesiclepedia, EVpedia and exoRBase, that is freely available to scientists globally. While there are several common lipids and proteins, there is also specific cargo only found in ocular EVs.…”
Section: Biogenesis Of Evsmentioning
confidence: 99%
“…40 Studies have already shown that ocular EVs, similar to EVs elsewhere in the body, are heterogeneous in nature and may contain various cargo such as genetic material, lipids, proteins and small metabolites. 41,42 Other enriched EV cargo includes cholesterol, Rab proteins, 49,52 syntenin-1, 32 clathrin, 52,56 ubiquitin, 56 ALIX, 49,52,56 TSG101, 49,56 ARF6, 31,32 PLD2 32 enzymes GAPDH, 13 Enolase, 57 ATPase, 57 PK, 57 MMP-14, 58,59 C3/C5 Convertase, 57 PDK1, 60 ERK1/2, 60 AMPK1, 60 MMP-1, 13 MMP-2, 13 sphingomyelin 30 other relevant cargo annexins (I, II, IV, V), 52 syntaxin proteins, 13 FASL, 13 complement factors (H, I, C3, C5), 53 emilin-1, 61 neuropilin-1, 61 VEGF-R1, 53 EFEMP1, 53 pro-inflammatory cytokines (IL-6, IL-8, TNF-α), endostatin, 62 PEDF and TIMP-1, 62 CXCL6, 63 CXCL12, 63 fibronectin, 64 thrombospondin-1, 64 ceramide 30 sphingomyelin, ceramide, and lipid raft proteins. 43,44 Given the varying cargo between different EVs, scientists have developed a consortium of EV databases including ExoCarta, 45 Vesiclepedia, 46 EVpedia 47 and exoRBase, 48 that is freely available to scientists globally.…”
Section: ■ Biogenesis Of Evsmentioning
confidence: 99%
“…The number, size and biologically active material of EVs are altered in numerous inflammatory conditions. Moreover, EVs affected the cellular functions of neutrophils, monocytes, macrophages and their precursor hematopoietic stem and progenitor cells ( Akbar et al, 2021 ). TNF-α stimulation increases the number of exosomes secreted from GMSCs and enhances exosomal expression of CD73, thereby inducing anti-inflammatory M2 macrophage polarization ( Nakao et al, 2021 ).…”
Section: Mechanism By Which Evs Promote Dental and Maxillofacial Tiss...mentioning
confidence: 99%